Outsourcing informatyczny jako koncepcja zarządzania obszarem IT w organizacjach gospodarczych - Dziembek, Damian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article presents the information system outsourcing as a conception of management information and communication technology in a company. The starting point is an introduction of idea and areas of outsourcing. Next the paper presents characteristics, types, advantages and threats of the information system outsourcing. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 140-158